Studi Ayat-Ayat Makkiyah Dan Madaniyyah Melalui Pendekatan Historis - Khoirun Nisa; Dedi Masri; Muhammad Alfiansyah; Meysah Wanda Sari; Siti Anisah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This study describes the study of Makkiyah and Madaniyah verses with a historical approach. Qualitative research is the type of research used in this study. Meanwhile, the collection method used involved several sources, such as relevant books and journals. The findings of this study include: (1) Deeper Contextual and Historical Understanding in Understanding Makkiyah and Madaniyah Verses, (2) The Importance of Makkiyah and Madaniyah Studies in Islamic Education.